EFFECT OF DE-tert-BUTYLATION AND FUNCTIONALIZATION WITH AMINE GROUPS AT THE UPPER RIM OF p-tert-BUTYLCALIX[4]ARENE TO THE EXTRACTABILITY FOR Cr3+, Cd2+ and Pb2+ IONS - Firdaus Firdaus; Jumina Jumina; Hardjono Sastrohamidjojo (Universitas Gadjah Mada, 2007)
The effects to the extractability forwards Cr3+, Cd2+, and Pb2+ ions of de-tert-butylation and functionalization with amine groups at the upper rim of p-tert-butylcalix[4]arene had been studied by applied the p-tert-butylcalix[4]arene (1), tetrahydroxycalix[4]arene (2), and p-(amino)butoxycalixarene (3) compounds as extractants for the heavy metals ions. The extraction involved optimise of three parameters, i.e. pH, time, and concentration of extractants. The extraction degrees of the heavy metals ions at optimum conditions were compared each other to decide the effects. Compound 1 showed high extractability to Cr3+ and Pb2+ ions over Cd2+ ion, but compound 2 as the debutylated product of compound 1 showed low extractability to the all of the heavy metals ions. Compound 3 as product of etherification with butyl groups of the lower rim followed functionalization with amine groups of the upper rim of compound 1 showed high extractability to Pb2+, but low to Cr3+ and Cd2+. Pursuant to the facts it was concluded that debutylation of compound 1 to compound 2 causing decrease drastically of extractability to the heavy metals ions; functionalization of the upper with amine groups as ionophore (compound 3) causing increase of the extractability to Pb2+ ion and decrease of the extractability to Cr3+ with increasing of separation factor value β(Pb2+/Cr3+) from 1.74 by compound 1 to 48.00 by compound 3. By slope analysis, the extracted species and mechanisms of the extractions have been confirmed.